Composite model of radio-frequency path nonlinearity for discrete analysis of electromagnetic compatibility - E. V. Sinkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Nonlinearity model synthesis techniques used in the framework of the discrete technology of electromagnetic compatibility analysis are compared by an example of the UHF amplifier: the models synthesized by the different techniques are collated according to the types of reproduced nonlinear effects and according to the accuracy of nonlinear interference level approximation. Based on the results of the comparison, a technique for synthesis of composite nonlinear models is developed. Such models provide a high accuracy of approximation of the device-under-modeling amplitude-to-amplitude responses for the desired signal and for the nonlinear interference both in the small-signal region and in the desensitization region.